Culturally Adapting an Advance Care Planning Communication Intervention With American Indian and Alaska Native People in Primary Care. (March 2020) - Lillie, Kate M.; Dirks, Lisa G.; Curtis, J. Randall; Candrian, Carey; Kutner, Jean S.; Shaw, Jennifer L.
Introduction: Advance care planning (ACP) is a process in which patients, families, and providers discuss and plan for desired treatment goals. American Indian and Alaska Native people (AI/AN) have higher prevalence of many serious, life-limiting illnesses compared with the general population; yet AI/ANs use ACP considerably less than the overall population.Method: We conducted a qualitative study to culturally adapt an existing ACP intervention for AI/ANs in two primary care settings.Results: We found that it is important to incorporate patients' cultural values and priorities into ACP, determine who the patient wants involved in ACP conversations, and consider the culturally and locally relevant barriers and facilitators when developing an ACP intervention with AI/AN communities.Discussion: At the core, ACP interventions should be clear and understandable across populations and tailored to facilitate culturally appropriate and meaningful patient–provider communication. Our results and methodology of culturally adapting an intervention may be applicable to other underrepresented populations.